FLYPAPER EFFECTS ANOMALY OF WEST PAPUA CAPITAL PUBLIC EXPENDITURE - Marthen Anthon Pentury (Economic Journal of Emerging Markets, 2011)
In fiscal decentralization, local governments should be able to provide public service facilities for all communities. This study aims to determine the existence of flypaper effect in the total capital public expenditure and capital expenditure on education, health and infrastructure in districts in West Papua, 2003-2006. Tools of analysis used is panel data regression. The General Allocation Fund (DAU), the Special Allocation Fund (DAK) and the Special Autonomy Fund (DOK) partially and simultaneously have positive impact on total capital spending and capital expenditure in education, health, and infrastructure. It is also indicated the anomaly of flypaper effect in DAU, DAK, and DOK.Keywords: Flypaper effect, anomaly, fiscal decentralization, capital expendituresJEL classification numbers: H50, H75